Violin and viola - Menuhin, Yehudi, 1916-1999; Primrose, William, 1904-1982; Stevens, Denis, 1922-2004; Vatelot, E. (Etienne) (London : Kahn & Averill, 1991)
Preparation of the violinist - First facts - Technique - Practising - Violinist in action - Repertoire and interpretation - Making, repair and care of the violin and bow - Viola
The instrument / Etienne Vatelot -- The violin / Yehudi Menuhin. First facts -- Technique -- Practising -- The violinist in action -- Repetoire and interpretation -- The making, repair, and care of the violin and bow -- Teaching -- Lessons at the Yehudi Menuhin School -- The viola / William Primrose. The viola -- A short history / Dennis Stevens. Early history -- Bach's sonatas and partitas for violin
Originally published: London : Macdonald and Jane's, 1976
Includes index, bibliography (pages 233), and discography (pages 235-243)
Keywords: Violin -- Instruction and study; Viola -- Instruction and study